Selection and Bioassay of Azotobacter sp. Isolates to Improve Growth of Chili (Capsicum annum L.) on Entisols in Ambon - REGINAWANTI HINDERSAH; PRIYANKA PRIYANKA; WILHELMINA RUMAHLEWANG; A MARTHIN KALAY (Indonesian Society for microbiology, 2016)
Leafy vegetables contributes to the inflation rate in Ambon City due to low productivity in rainy season. Some vegetables are imported from other islands while importantvegetables such as local petsai (Brassica chinensis L.) and chili (Capsicum annum L.) are cultivated in low nitrogen soil, Entisols. Lack of nitrogen could be overcome by using inorganic fertilizeras well as biofertilzer. The soil can be inoculated with rhizobacteria, such as Azotobacter, to increase the nitrogen uptake and improve the quality of vegetables. This research was conducted to isolate and select Azotobacter from rhizosphere of vegetables and to examine the effect of Azotobacter inoculation on chili-seedling growth and nitrogen uptake by using bioassay method. Azotobacter sp. was isolated in nitrogen-free Ashby’s Media. The bioassay was held in the green house with randomized block design experiment, which examined the combination of isolates and population of Azotobacter sp. on chili. Two best isolates which was selected based on pH, nitrogen content and cell viability were s2a10 (from petsai's rhizosphere) and c2a9 (from chili’s rhizosphere). Bioassay showed that Azotobacter inoculation followed by reduced NPK fertilizer doses had no effect on transplant dry weight and nitrogen uptake. All Azotobacter 8 -1inoculation except 10 CFU mL s2a10 maintain soil nitrogen although Azotobacter population in soil was slightly reduced. This showed that Azotobacter sp. potentially reduce the use of inorganic biofertilizer.